Evaluation of mortality among patients in the emergency unit in Al-Kindi Teaching Hospital, Baghdad, Iraq - Abeer A. Gatea; Mustafa A. Abdullah (Al Ameen Medical College, 2018)
Background: During the fifteen year, the deterioration of health system in Iraq due to war and Daesh and the lack of facilities and equipment's led to increasing the mortality and morbidity among people in emergency units. Aims: To identify the causes of mortality among cases in the emergency units. Methodology: A cross-sectional study was conducted in Al-Kindi teaching hospital in Baghdad for one year. The information was collected from the emergency unit record as well as the patient's card. Stata version 14 was used for analysing this data. Results: The mean age of dead patient was 42.47 ± 21.5 years (minimum 3 and maximum 81). The mortality of male 65/120 (54.2%) was more slightly than female55/120 (45.8%). 75/120 (62.5) had married and 39/120 (32.5%) had a single status. Also, 30/120 (25%) was dying due to cerebrovascular disease then followed by 18/120 (15%) for each traffic accident, diabetes and burn. Conclusions: the majority of death was higher among age groups < 40 years and also, the main causes of death is cerebrovascular disease followed by traffic accident and burn. There is a significant relation between ages, gender, and marital status with the causes of death.